IPTEKS PROSEDUR PEMBAYARAN PAJAK KENDARAAN BERMOTOR YANG TERUTANG PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH PROVINSI SULUT - Makausi, Alma Meita; Bukidz, Hendra Wati; Sabijono, Harijanto (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
This study aims to find out about taxes and how the application of payment procedures and imposition ofÂ  motor vehicle tax penalties that have passed the maturity of the Tax and Retribution Management Agency in North Sulawesi Provinci Based on estabilished local government provisions and regulations, where existing procedures can make it easier to oblige tax in carrying out payments so that the procedure runs well. Texpayers are expected to be able to comply with existing procedures and provisions, so that there is no delay in paying taxes. Taxes that are local revenue are also expected to be able to improve the regional development structure of North Sulawesi,so that regional government development plans can be realized.Keywords: Vehicle Tax,Payment Procedure,Tax Payable